China's cooperation in Africa in the area of physical connectivity infrastructure. The case of the Mombasa-Nairobi railway line - Dussort, María Noel (2019)
In the 21st century, China proposes a cooperation scheme with its own characteristics. In relation to the cooperation projects that China has been carrying out in the African continent, an exponential growth of infrastructure works was observed that has contributed to the improvement of the socio-economic conditions of Africa. In this context, it is worth asking, what distinctive characteristics does Chinese cooperation in infrastructure have that makes it so attractive to African countries? For the purpose of answering this question, we propose to analyse the link that Beijing has established with the African countries, specifying the characteristics its cooperation scheme presents. Likewise, the priority areas around which cooperation projects are directed and their financing modality are investigated. Secondly, we consider the construction of one of the sections of the railway in Kenya (Mombasa-Nairobi project) under the Belt and Road Initiative (BRI) as a typical case of China's infrastructure cooperation in an African country.